Development of Flashcard Media Based on Game Based Learning to Improve Mathematics Outcomes among Elementary School Students - Chasanah, Nur; Sulianto, Joko; Siswanto, Joko (FKIP - Universitas Riau, 2025)
Low student achievement in Mathematics at the elementary level is often associated with the use of conventional learning methods that do not optimally stimulate student engagement and conceptual understanding. Therefore, innovative learning media are needed to support more interactive and meaningful learning. This study aims to develop and test the effectiveness of Flashcard media based on Game-Based Learning (GBL) to improve mathematics learning outcomes among elementary school students. The research employed a Research and Development (R&D) method using the ADDIE model, involving two teachers and 30 second-grade students at SD Negeri Sendangmulyo, Rembang Regency. The developed Flashcards featured colorful visuals, arithmetic operations, and game-based elements to encourage active participation. Expert validation obtained an average score of 3.89 (very feasible), while practicality testing yielded scores of 3.95–4.00 (very practical). The effectiveness test showed an increase in the average student score from 49.63 (pretest) to 78.83 (posttest), with an N-Gain of 0.60 (moderate–high). These results indicate that the Flashcard media based on Game-Based Learning is valid, practical, and effective in improving students’ mathematical understanding and learning motivation in accordance with the principles of the Merdeka Curriculum.